Individual Behavior and Group Behavior in the Organizational Behavior of Educational Leadership at Al-Jaohar IT Middle School - Ridwan Ahmad; Sihabudin; Siti Aminah; Tamsikuddin; Masduki Dzuriyat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to explore the behavior of teachers and students at AL-Jaohar IT Middle School, focusing on evaluating their performance in the context of school organization. Through a qualitative approach, the study found that individual and group behaviors have a significant impact on organizational dynamics in these schools. Factors such as motivation, heredity, environment, and education play an important role in shaping their behavior. AL-Jaohar IT Middle School, an educational institution with a relatively young Islamic boarding school system approach, shows the vital role of the Intra-School Student Organization (OSIS) in shaping students' leadership attitudes and developing their potential. However, infrastructure constraints such as inadequate facilities are a challenge in optimizing OSIS performance. Teachers' behavior is also influenced by personal, work, structural and work experience characteristics. Principal leadership with a participatory, democratic, militaristic and charismatic approach plays an important role in directing teacher and student performance towards achieving organizational goals. Collaborative strategies in task assignment, motivation, and support for professional development have also proven effective in increasing teacher work participation. The conclusions of this study confirm that a deep understanding of the factors that influence individual behavior in an educational context is essential. Recommendations were presented to improve the quality of school facilities as well as to expand the principal's consultation network with school committees, foundations and academic elements to further the performance of educational organizations.